Can adding web-based support to UK primary care exercise referral schemes improve patients' physical activity levels? Findings from an internal pilot study. - Adrian Taylor; Douglas Webb; Sarah Dean; Kate Jolly; Nanette Mutrie; Lucy Yardley (Frontiers Media S.A., 2015)
Background: Promoting physical activity (PA) via primary care exercise referral schemes (ERS) is common but there is no rigorous evidence for long term changes in PA (Pavey et al, 2011) among those with chronic conditions. From July 2015, for 15 months, the e-coachER trial began to recruit 1400 patients (in SW England, Birmingham and Glasgow) with one or more chronic conditions including diabetes, obesity, hypertension, osteoarthritis, or depression, who are eligible and about to attend an ERS. The two-arm parallel RCT is powered to determine if the addition of a web-based, interactive, theory-driven and evidence-based support system called e-coachER (hosted on the 'LifeGuide' platform) will result in at least 10% more patients who do 150 mins or more per week of accelerometer assessed moderate or vigorous physical activity (MVPA) at 12 months. Recruitment into the trial is within primary care, using both mail-merged patient invitations and opportunistic GP invitations (and exercise referrals). Within the trial, after participants are screened, provide consent and complete baseline assessments, they are randomised to receive usual ERS at each site or usual ERS plus a mailed Welcome Pack with registration details to access e-coachER on-line. Inclusion criteria for entering the trial are: (1) Aged 16-74 years; (2) with one or more of the following: obesity (BMI 30-35), hypertension (SBP 140-179 or DBP 90-109, type 2 diabetes, lower limb osteoarthritis, recent history of treatment for depression; (3) Participants who are in the two lowest (of four) groups using the GP Physical Activity Questionnaire; (4) have an e-mail address and access to the internet; (5) Eligible for an ERS. The intervention rationale, design and content are reported in another presentation. Aims: This presentation will provide initial findings from a 3 month internal pilot phase with a focus on trial recruitment and initial intervention engagement. We will present data on the achievement of our targets for recruiting 180 participants across the three sites and proportion who initially go online to register and use e-coachER. We also aim, based on detailed process evaluation work, to present a summary of factors influencing recruitment and intervention engagement, and any adaptations needed for the recruitment process. Methods: Data is being captured to inform a CONSORT chart with details on number of patient invitations, number and reasons for trial exclusion, and numbers and characteristics of those recruited. The LifeGuide system will provide data on numbers/proportion assigned to the intervention arm who register and start to use e-coachER. Qualitative data on recruitment processes and intervention engagement, as part of the process evaluation, will be summarised. Results: Due to a number of factors recruitment began 2-4 months later than planned across the 3 sites. Data will be presented on achieved recruitment and e-coachER engagement relative to our targets in the internal pilot trial. Qualitative data will be presented on the acceptability and feasibility of the trial methods and intervention. Conclusion: A summary of what we have learned about recruitment and intervention engagement will be presented and ideas for improvement, as appropriate. Supported with funding from the NIHR (HTA) Project: 13/25/20